Cultivating leadership qualities in students-future Horting coaches and physical education teachers - Malynskyi, Ihor Yosypovych; Veselova, Viktoriia Viacheslavivna (Liha-Pres, 2025)
The authors of the publication, based on an analysis of literary sources, identified leadership qualities that need to be cultivated in students – future Horting coaches and physical education teachers: honesty; communication / sociability; knowing your strengths and weaknesses well; active listening; possessing theoretical knowledge and practical skills about Horting – Ukrainian martial art; friendliness, responsiveness, attentiveness; a Horting trainer is a spiritually and physically healthy person; individual approach; empowerment; delegation; self-confidence; emotional intelligence; decision-making and problem-solving skills; self-motivation, etc. The statements of Horting trainers have been made public: a good leader is not born, one must persistently become one; a person who has leadership qualities does not necessarily have to have a high IQ; a good leader must always remain a person whom people will respect and strive to imitate, etc.

Авторами публікації, на основі аналізу літературних джерел, визначено лідерські якості, які потрібно виховувати у студентів – майбутніх тренерів з хортингу та учителів фізичної культури: чесність; спілкування / комунікабельність; добре знати свої сильні та слабкі сторони; активне слухання; володіти теоретичними знаннями та практичними вміннями про хортинг – українське бойове мистецтво; доброзичливість, чуйність, уважність; тренер хортингу це духовно і фізично здорова людина; індивідуальний підхід; розширення можливостей; делегування; впевненість у собі; емоційний інтелект; навички прийняття рішень і вирішення проблем; самомотивація і т. д. Оприлюднено твердження тренерів хортингу: гарний лідер не народжується, ним потрібно наполегливо ставати; людина, яка має лідерські якості не обов’язково повинна мати високе IQ; гарний лідер повинен завжди залишатися людиною, якого будуть поважати та прагнути наслідувати і т. д.
Keywords: students; future Horting coaches; physical education teachers; leadership qualities; honesty; communication / sociability; own strengths and weaknesses; active listening; possess theoretical knowledge; possess practical skills; spiritually and physically healthy person; friendliness; responsiveness; mindfulness; individual approach; empowerment; delegation; self-confidence; emotional intelligence; self-motivation; студенти; майбутні тренери з хортингу; учителі фізичної культури виховання; лідерські якості; чесність; спілкування / комунікабельність; власні сильні та слабкі сторони; активне слухання; володіти теоретичними знаннями; володіти практичними вміннями; духовно і фізично здорова людина; доброзичливість; чуйність; уважність; індивідуальний підхід; розширення можливостей; делегування; впевненість у собі; емоційний інтелект; самомотивація